Fostering National Identity Through Civic Disposition and Unity in Diversity: A Strategic Model for Football Supporters of Pss Sleman and Psim Yogyakarta - Nurgiansah, T Heru; Danial, Endang; ., Rahmat; Mahpudz, Asep; Suryadi, Karim (Journal of Posthumanism, 2025)
This study aims to develop a strategic model based on Civic Disposition and Unity in Diversity to strengthen national identity among football supporters, with a particular focus on the rivalry between PSS Sleman and PSIM Yogyakarta. Using a qualitative approach with Constructivist Grounded Theory, data were collected through semi-structured interviews and participant observation involving 15 informants, including supporter leaders, club officials, academics, and security authorities. Through rigorous coding and thematic analysis, the study identified five key strategies: educational interventions, symbolic cultural actions, formal mediation, positive media engagement, and mass mobilization. These strategies demonstrated how supporter rivalries, traditionally sources of division and conflict, can be redirected toward constructive expressions of national solidarity. The findings extend Civic Disposition theory into informal supporter contexts, operationalize Unity in Diversity through grassroots action, and enrich applications of Social Identity and Multicultural Citizenship theories within sports sociology. The study concludes that football supporter communities represent a vital yet underutilized platform for fostering civic virtues and national cohesion. Practical implications for supporter organizations, football clubs, and local governments are discussed, highlighting the importance of sustained, participatory efforts to cultivate civic culture within Indonesia’s vibrant football landscape. Future research directions include longitudinal studies and comparative analyses across different regions.